البيع بالإيجار للسكنات المنجزة بأموال عمومية - شنوف صورية; يوسف إيمان (جامعة الوادي University of El Oued, 2025)
ناولت هذه المذكرة موضوع البيع بالإيجار للسكنات المنجزة بأموال عمومية، كآلية قانونية اعتمدتها الدولة الجزائرية لتمكين المواطنين من الحصول على سكن مع إمكانية تملكه بعد دفع أقساط إيجاريه وتهدف الدراسة إلى توضيح الإطار القانوني لهذا النظام وتحليل طبيعته، وشروطه، والحقوق والالتزامات المترتبة عنه. تم اعتماد المنهج التحليلي والوصفي لفهم النصوص القانونية المنظمة للعملية، ورصد الإشكالات العملية المرتبطة بها، وخلصت المذكرة إلى أن البيع بالإيجار يشكل حلا مناسبا لتوفير السكن مع الحفاظ على المال العام، لكنه يحتاج إلى تحسينات قانونية وميدانية لضمان نجاحه. This memorandum addresses the issue of rent-to-own housing units built with public funds, a legal mechanism adopted by the Algerian state to enable citizens to acquire housing with the possibility of ownership after paying rental installments. The study aims to clarify the legal framework of this system, analyze its nature, conditions, and the rights and obligations arising from it. An analytical and descriptive approach was adopted to understand the legal texts regulating the process and to identify the practical problems associated with it. The memorandum concludes that rent-to-own constitutes a suitable solution for providing housing while preserving public funds, but it requires legal and practical improvements to ensure its success.
قانون عقاري
Keywords: لبيع بالإيجار- الترقية العقارية –التوثيق – المرقي العقاري- الموثق- الإشهار العقاري.; For sale by rent - Real estate development - Documentation - Real estate developer - Notary - Real estate advertising.